2012
DOI: 10.1002/rcm.6240
|View full text |Cite
|
Sign up to set email alerts
|

Mitigation of signal suppression caused by the use of trifluoroacetic acid in liquid chromatography mobile phases during liquid chromatography/mass spectrometry analysis via post‐column addition of ammonium hydroxide

Abstract: A method has been developed to reduce the mass spectrometric ion signal suppression associated with the use of TFA as an additive in LC mobile phases. Through post-column infusion of diluted NH(4)OH solution to LC eluents, the ammonium ion introduced causes the neutral analyte-TFA ion pair to dissociate which consequently releases the protonated analyte as free ions into the gas phase (through regular electrospray ionization mechanisms). An ion signal improvement from 1.2 to 20 times for a variety of compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…Several studies proposed that mobile phase additives that affected the ionization of analytes in ESI by changing the ionic form of the analytes as well as the property of the mobile phase, such as pH, conductivity, surface tension of the solution, the concentration of electrolytes, and adduct formation [33,34,41]. However, it was found that the solutions (with and without phthalic acid) had almost the same pH, conductivity and surface tension values (Tables S3 and S4).…”
Section: The Mechanism For the Improved Performance Of Phthalic Acidmentioning
confidence: 66%
“…Several studies proposed that mobile phase additives that affected the ionization of analytes in ESI by changing the ionic form of the analytes as well as the property of the mobile phase, such as pH, conductivity, surface tension of the solution, the concentration of electrolytes, and adduct formation [33,34,41]. However, it was found that the solutions (with and without phthalic acid) had almost the same pH, conductivity and surface tension values (Tables S3 and S4).…”
Section: The Mechanism For the Improved Performance Of Phthalic Acidmentioning
confidence: 66%
“…However, the use of smaller pore size column can lead to poor elution of ADC molecule and reduction of column life time [17]. Utility of TFA is not preferred because of the formation of protein-TFA adducts and ion signal suppression [18]. Another method such as on-line size exclusion chromatography (SEC)-MS [19] is relatively straightforward and could be used to separate PNGaseF from ADCs.…”
Section: Resultsmentioning
confidence: 99%
“…To address this, several post-column strategies to perform efficient LC-MS using TFA-containing mobile phases have been proposed. These approaches include dilution [12][13][14], electrophoretic mobility control [15], membrane-based dialysis [16,17], and exposure of the nebulized LC effluent to gas vapors (e.g., ACN, propionic acid) during ESI [18,19]. Most of these reports are limited to low-flow applications, use flow splitters, or require complicated setups, hindering their general use.…”
Section: Introductionmentioning
confidence: 99%